Broken soup - Valentine, Jenny (London : HarperCollins Children's Books, 2011)
A photographic negative and two surprising new friends become the catalyst for healing as fifteen-year-old Rowan struggles to keep her family and her life together after her brother's death.
Young Adult.
Young Adult
Keywords: Dysfunctional families -- Juvenile fiction; Grief -- Juvenile fiction; Family problems -- Fiction; Grief -- Fiction; Family problems -- Fiction; Grief -- Fiction; England -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction